Physical health of prisoners, 1994 (UK Data Service, 1998)
The purpose of this study was to collect baseline data on the physical health of sentenced male prisoners, to assess their physical needs, to investigate health-related behaviour, to assess the extent and nature of physical disorder and to compare them with men of equivalent age in the general population. Comparisons were made with the general population using the data for the Health Survey for England, 1993 carried out by OPCS (held at the Data Archive under SN:3316).